Crimean-Congo hemorrhagic fever in Turkey - (:unkn) unknown (Springer Netherlands, 2007)
The first published seroepidemiologic study on Crimean-Congo hemorrhagic fever (CCHF) in Turkey was performed in the Agean region of Turkey in the 1970s [30]. According to this study, Crimean-Congo hemorrhagic fever virus (CCHFV) antibodies were detected in 96 out of 1,074 (9.2%) human serum samples, by hemaglutination inhibition test. Likewise, neutralizing antibodies against the virus were detected in 13 out of 96 (13.5%) samples. However, prior to 2002, no clinical cases of CCHF or virus detections in ticks were reported from Turkey. © 2007 Springer Netherlands. All rights reserved.